A Novel Design of FANET Routing Protocol Aided 5G Communication Using IoT - Khan, Inam Ullah; Abdollahi, Asrin; Jamil, Abdul; Baig, Bisma; Aziz, Muhammad Adnan; Subhan, Fazal (Journal of Mobile Multimedia, 2022)
Flying-Thing is a new promising area, while in last few years Unmanned Aerial Vehicles are emerged. UAVs are very efficient in completing tasks also organizing ad hoc behaviour of networks, thus making flying ad hoc networks. The formation of aerial nodes is not feasible until we use Mobility models for communication between UAV’s. Mobile ad hoc networks & wireless sensor networks are mostly static in behaviour but UAVs are dynamic and deployed in sky using mobility models. In flying ad hoc networks effective communication can be made possible using 5G networks while designing routing protocols. In this paper a comprehensive study is formally introduced covering routing protocols used in flying ad hoc networks, mobility models, heuristic computations, architecture and optimization techniques for improving parameters in flying ad hoc networks. This paper reflects and explains future challenges and help scientists, Researchers to discover more research gaps that have been discussed in the literature and need more investigation. Also, different applications of flying things can be used in IoT based forestry which includes forest mapping, management where optimal results can be obtained. The uniqueness of this research study is to provide heuristic computational algorithm called AntHocNet, Mobility models, drawbacks of traditional technologies, flying-things architecture will be the core interest of this research study.